Zasady świadczenia usług w zakresie gier hazardowych w prawie Unii Europejskiej - Barwaśny, Dariusz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The paper presents principles of providing gambling services in European Union law. This article is based not only on a legal perspective, but also shows external factors that make the present subject so attractive. Ethic, religious aspects and a strong economic background of this topic seem to have impact on legal regulations. European Union law does not contain a particular „gambling act”, thus the Court of Justice of the European Union functions de facto as a lawmaker. A quite significant number of judgements in this area allows to decode some common rules on the basis of which the Member States are entitled to limit an organization of this type of entertainment. Fundamentals for this competence are established by the doctrine of overriding reasons in the public interest, restricted, however, by the requirements of nondiscrimination, proportionality and cohesion of restrictions. The elements mentioned before result in a fact that the CJEU’s decision–making presents a few special features, concerning inter alia a wide margin of appreciation and evidentiary issues.
Keywords: gry hazardowe; świadczenie usług; wymogi imperatywne; nadrzędne względy interesu ogólnego; niedyskryminacja; margines uznania; prawo Unii Europejskiej